Budaya Wudhu dengan Cara Duduk sebagai Bagian dari Identitas Keislaman di Saiyid Wittaya Fondatun School Songkhla Thailand - Habibah, Julita Nabila; Rofi’ah, Siti Hamidahtur; Arifin, Zainal (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The practice of ablution by sitting is not just a ritual of worship, but also contains an interesting cultural dimension at Saiyid Wittaya Fondatun School, Songkhla – Thailand, this practice becomes part of the daily life of students and reflects the values of Islamic culture that have been passed down from generation to generation. This research aims to explore the practice of ablution by sitting can form students' Islamic identity as well as part of school culture. This research uses a qualitative method with a case study approach. The data was collected through participatory observation, in-depth interviews and analysis of related documents. The results of the study show that ablution by sitting has become a symbol of a distinctive Islamic identity in Saiyid Wittaya Fondatun School, not only as a religious practice but also as an integral part of the school's culture and discipline. This practice is to respect local traditions and maintain a balance between spiritual and social practices in the educational environment as well as to be a form of unique school identity and an example of the integration of religious and cultural values in education